4x+5=6x-11

Simple and best practice solution for 4x+5=6x-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+5=6x-11 equation:


Simplifying
4x + 5 = 6x + -11

Reorder the terms:
5 + 4x = 6x + -11

Reorder the terms:
5 + 4x = -11 + 6x

Solving
5 + 4x = -11 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
5 + 4x + -6x = -11 + 6x + -6x

Combine like terms: 4x + -6x = -2x
5 + -2x = -11 + 6x + -6x

Combine like terms: 6x + -6x = 0
5 + -2x = -11 + 0
5 + -2x = -11

Add '-5' to each side of the equation.
5 + -5 + -2x = -11 + -5

Combine like terms: 5 + -5 = 0
0 + -2x = -11 + -5
-2x = -11 + -5

Combine like terms: -11 + -5 = -16
-2x = -16

Divide each side by '-2'.
x = 8

Simplifying
x = 8

See similar equations:

| x^2+7xy+6y^2=0 | | 11x=185 | | 4-6x/5=7 | | 6x-1=-q+20 | | -5b^2-4b-5=0 | | 150x=1800 | | 6f+7/7-5f-f | | 10.2s=61.2 | | x^2-15xy+26y^2=0 | | 4(-3/5)(3a+4)=7 | | -8(3+7x)+5=39+2x | | -2v-4=-2v | | 4x+27=x+12 | | 5(2x-2)=3(4-2x) | | -2-5n=-5n^2 | | 3x+9/15=6 | | 8x^2+8xy-20y=0 | | -x+9=1/3(-9x+6)+1 | | -3(3r+3)=5-7r | | 5x-1-4x=x+17 | | 16-7*2= | | N^2+6=5N | | -3n+9+8n=7n-8n-9 | | 12x+2=4x-22 | | n+7/4=7/20 | | 5x=5/8 | | (4y-1)+(2x+5)=180 | | 6n-2=6n-7 | | 6w^2+24w-72=0 | | A^2-3A-3=5 | | 2x-16-x=x-16 | | 5x^2+24=0 |

Equations solver categories